PENDAMPINGAN PENYUSUNAN STANDAR PELAYANAN DI DESA DOROKOBO KABUPATEN DOMPU DALAM MEWUJUDKAN PELAYANAN PRIMA - Gufran,; syamsuddin,; Kasmar,; Rahmat Akbar, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Making public service standards is an obligation given by law to service providers. But in reality, there are still many service products that do not have service standards. Often a problem in the field. People often do not know what to do. Knowing service standards is a right owned by the community. The activities that will be carried out in this service program are to make public service standards in Dorokobo Village, Kempo District, Dompu Regency. by actively involving the community in every activity stage and providing assistance to village officials to make public service standards. This activity aims to assure the implementation of public services in Dorokobo Village to be a benchmark in assessing service quality. In becoming an instrument of supervision for the community by using predetermined indicators, reducing the potential for maladministration